Attitudes towards Future Unemployment and European Cooperation to Reduce Unemployment among 8th Graders in EU/European Countries - Aleš Trunk; Eva Klemenčič Mirazchiyski; Plamen Vladkov Mirazchiyski (MDPI AG, 2022)
The focus of this article is on the attitudes among 8th graders in European countries on future unemployment and attitudes towards cooperation among European countries to guarantee high levels of employment and strengthen their economies. This article uses both qualitative and quantitative approaches. For the qualitative approach, a systematic literature review was performed using four databases, starting from 16,873 search results for the 2016-2021 period before systematically limiting them to identify possible predictors used in quantitative analyses. The quantitative part uses secondary analyses of data obtained from 52,788 upper secondary students from 14 EU and one EU associated country from the International Civic and Citizenship Education Study (ICCS) 2016, which is the last available cycle with publicly available data since 2018. The techniques used to analyse the data are descriptive statistics, linear and binary logistic regression, Pearson's and Spearman's correlation coefficients, and Principal Component Analysis. This article also considers the theoretical base of the sustainable development definition-it explores youths' present perceptions of the future in the economic and financial domains.